Acute Respiratory Distress Syndrome in Two Rhesus Macaques (Macaca mulatta) - Fremont, Jacqueline J (American Association for Laboratory Animal Science, 2008)
Acute respiratory distress syndrome (ARDS) is an important and potentially life-threatening complication in humans that arises subsequent to a variety of primary insults including noxious fume inhalation, infection, and trauma. Here we describe the first two cases of ARDS reported in association with postoperative complications in rhesus macaques. In agreement with the multifactorial nature of the human syndrome, ARDS in one monkey was attributed to sepsis, whereas in the other it was ascribed to neurogenic trauma. Despite the different etiologies, both monkeys demonstrated clinical features of ARDS, including progressive dyspnea and pulmonary edema, and syndrome-defining histopathologic criteria including edema with intraalveolar neutrophils, fibrinohemorrhagic effusions with crescentic membranes, and interstitial vascular degeneration. Recognition and aggressive treatment of ARDS at an early stage may improve survival rates in dyspneic nonhuman primates with underlying extrapulmonary diseases.